2021
DOI: 10.13057/biotek/c180103
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Analysis of purity and concentration of DNA extracted from intron patho gene-spin extraction on crab processed food product samples

Abstract: Abstract. Sophian A, Purwaningsih R, Muindar, Igirisa EPJ, Amirullah ML. 2021. Short Communication: Analysis of purity and concentration of DNA extracted from intron patho gene-spin extraction on crab processed food product samples. Asian J Trop Biotechnol 18: 28-31. The purpose of this study was to optimize the Intron patho gene-spin DNA/RNA extraction kit on crab processed food products so that it can be used for testing samples other than viral and bacterial samples. The method used in purity and concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, according to Abdel-Latif and Osman (2017); Aboul-Maaty and Oraby (2019) [29][30], the purity of DNA is still included in a good purity coefficient, in the range of >1.5 and <1.9 or in the range of 1.8. DNA purity value between 1.8-2.0 is also included in high-quality DNA purity [31]. The concentration of DNA extracted from this research showed a range between 116-394 ug/ml.…”
Section: Dna Quality and Quantitymentioning
confidence: 76%
“…However, according to Abdel-Latif and Osman (2017); Aboul-Maaty and Oraby (2019) [29][30], the purity of DNA is still included in a good purity coefficient, in the range of >1.5 and <1.9 or in the range of 1.8. DNA purity value between 1.8-2.0 is also included in high-quality DNA purity [31]. The concentration of DNA extracted from this research showed a range between 116-394 ug/ml.…”
Section: Dna Quality and Quantitymentioning
confidence: 76%
“…This is because enzymes work quite effectively by directly targeting amino acid bonds in protein lysis. The proteinase K enzyme is active at a temperature of 65-70°C; thus, in some studies using this method, it is sometimes necessary to optimize the process before applying it (Utaminingsih et al, 2022;Sophian, et al, 2021b;Sophian, et al, 2021a;Sutanta et al, 2021). The purpose of this heating process is to activate the proteinase K enzyme so that it can efficiently perform lysis (Renshaw et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Sophian & Syukur (2021) shows that good-quality DNA isolation can be achieved from the meat of the target species. During DNA isolation, the main parameters that must be fulfilled are the concentration and purity values of the isolated DNA (Sophian, 2021c;Sophian, Purwaningsih, et al, 2021a;Utaminingsih et al, 2022) Based on the background above, this research was conducted to examine the quality of DNA isolated during the production of guinea pig DNA test standards. The purpose of this research is to offer an alternative reference for the manufacturing of species-specific DNA standards.…”
Section: Introductionmentioning
confidence: 99%
“…Low, moderate to high values of DNA yield were observed. A very large value of 2089.4 observed was considered by Alfi (2021) to be a very good yield. Low values of 6.1 ng/µl, 42.2 ng/µl, and 45.7 ng/µl from accessions Ab6, Ab4, and C46 respectively were similar to values (24.2 ng/µl, 43.11 ng/µl, 25.33 ng/µl, 27.25 ng/µl, and 36.18 ng/µl) observed in five tomato cultivars extracted with ZR kit method (Ganiyu et al, 2017).…”
Section: Electrophoresis Analysis Of Dna Extractsmentioning
confidence: 99%